Effect of Health and Safety Practices on Job Performance a Case Study of Pro Heli International Services Ltd Nakasongola - Danielle Kembabazi (Uganda Christian University, 2026)
The purpose of this research is to examine the effect of health and safety practices on job performance at Pro Heli International Services Ltd Nakasongola, Uganda assessing current practices, challenges, and improvement frameworks across aviation, hotel, and operations departments. It used a correlational design with stratified random sampling from 271 employees, collecting 117 questionnaire responses with 33 aviation staff, 36 operations staff, 18 hotel staff plus interviews and statistical analysis. Key findings highlight effective management provision of PPE in a timely manner, alongside opportunities for aviation staff to enhance consistent wearing of PPE shoes for optimal safety and performance. Conclusions confirm strong practices that boost motivation and performance, recommendations include PPE registers for fitting or replacement , regular training of PPE wear, better communication and fearless reporting for long-term results.
Undergraduate